Pengamanan Dokumen Dalam Upaya Mitigasi Bencana Alam Di Wilayah Rawan Bencana Kabupaten Pandeglang - Aghy Gilar Pratama; Sri Setiyowati; Dedeh Jubaedah; Andrianto Heri Wibowo (Jurnal Pengabdian Pada Masyarakat, 2022)
DOCUMENT SECURITY IN NATURAL DISASTER MITIGATION EFFORTS IN DISASTER-PRONE AREAS OF PANDEGLANG REGENCY.Pandeglang Regency is an area prone to natural disasters, ranging from floods, landslides, earthquakes and tsunamis, when natural disasters occur, documents tend to be damaged and lost, ranging from personal documents, commercial and government documents. Personal documents such as ID cards, diplomas, birth certificates and for commercial documents such as checks, notes and receipts, while Government documents are documents that contain state information from a government, such as regional regulations, government regulations and archives. Providing socialization and workshops is part of the steps for natural disaster mitigation efforts, especially document security, steps for securing documents using mobile communication tools, because mobile phones are tools that are already owned by all communities and village officials, but there are still many who do not understand the benefits of using mobile phones. the. The first stage of securing documents is that the mobile phone is connected to the internet, then access the Google Drive, to save the document, which has been scanned first using the scanner application installed on the cellphone of each community and village apparatus. This PKMS program is carried out in the form of workshops on document security in an effort to mitigate natural disasters in disaster-prone areas of Pandeglang Regency, the target of this activity is the community and apparatus of Pamarayan village, Jiput district, Pandeglang district. documents in disaster-prone areas, 2. Providing training related to document security to the community and village officials, 3. Growing understanding among the community and village apparatus about the use of digital technology.